Making participatory democracy come true – historical perspective and future prospect: the Brazilian internet regulatory framework (Revista da Faculdade de Direito, Universidade de São Paulo, 2010)
Making democracy true is a will for everyone around the world. Nowadays, communications’ revolution brought new artifacts for freedom of expression, a civil right that becomes global day-by-day. Therefore, democracy shapes up as fourth generation human right. It’s the participatory democracy, in which the citizen directly acts in the democratic game. This article intends to investigate the brazilian Internet Regulatory Framework, a brand new civil society’s joint initiative with the Executive that seeks to build a draft law about civil obligations and rights for national Internet actors. This is just an attempt to overcome the political party system, which passes through a lack of representativity and seems gently to lose legitimacy, a big risk for the survival of the democratic regime in the overcome.